Legislative Handbook on Principles of Equality and Non-Discrimination - Laibuta, Kibaya I. (My University, 2018)
August 2010 ushered in an unprecedented era of civil liberties backed by a robust Bill of Rights containing progressive provisions on economic, social and cultural rights. The transformative Constitution provided the foundational basis for reform in legislation and enhanced institutional frameworks for the respect, promotion and protection of human rights, including the right to equality and freedom from discrimination on the basis of gender and other social status specified in Article 27. These constitutional guarantees opened wide doors for heightened advocacy for the advancement of, among other things, gender equality and far reaching reforms towards gender mainstreaming and the safeguarding of women’s rights and the rights of other vulnerable and marginalised groups. The promulgation of the Constitution on 27 th Despite the broad spectrum of constitutional guarantees, which have heightened the legitimate expectations and aspirations of the people of Kenya, the majority are yet to enjoy equal opportunity and inclusion in all spheres of social-cultural, economic and political life. Indeed, Special Interest Groups (SIGs) do not enjoy equal access to fundamental rights and freedoms and remain subject to differential treatment and exclusion in the fields of healthcare, education, employment, economic and social life. Yet they are more than ever before entitled to recognition and equal protection of the law, which is only attainable through sound policy and legislation, administrative procedures and institutional frameworks founded on the core principles of equality and inclusion. To this end, state and non-state agencies have made concerted efforts to facilitate the realisation of human rights for marginalised groups and vulnerable minorities by influencing legislation and institutional reforms to motivate gender equality and inclusive development. To make these rights real, Article 59 of the Constitution established the Kenya National Human Rights and Equality Commission, which was subsequently restructured into the present-day Kenya National Commission on Human Rights (KNCHR), the National Gender and Equality Commission (NGEC) and the Commission on Administrative Justice (CAJ) to oversee the promotion and protection of human rights and freedoms.